Study of double-wall effusion cooling scheme for gas turbine blade applications - Ngetich, GC (2019)
Porous multi-wall cooling schemes such as double-wall cooling combined with effusion cooling offer a practical approximation to transpiration cooling which in turn present a potential for high cooling effectiveness. Most of the existing double-wall effusion cooling studies have been on flat plate geometries. There are varying external static pressure and secondary flow features in flow over an aerofoil which have an influence on overall cooling performance. Thus, there is need to study double-wall effusion cooling applied to an aerofoil. The main aim of this research was to extend the double-wall effusion-cooling technology research, that has long been undertaken on flat plates, onto a gas turbine blade.